Adoption of soybeans in subSaharan Africa: a comparative analysis of production and utilization in Zaire and Nigeria - Shannon, D.; Kalala, M. (1994)
The issue of soybean adoption in sub-saharan Africa is addressed. A survey was conducted of soybean (Glycine max (L.) Merr.) production and utilization in Gandajika, Zaire. Of 115 farmers sampled from nine villages, all cultivated soybean. Average production per farmer in the previous season was 73kg. Almost all production was consumed by humans, primarily as full-fat flour mixed with maize (Zea mays L.) or maize and cassava (Manihot esculenta (L) Crantz), or as roasted grain. Farmers ranked soybean second among grain legumes in area cultivated and fourth for total sales. Most farmers considered marketing the principal constraint to increased production. Survey results from Nigeria revealed similar adoption trends. Common elements were locally adapted foods in which soybean did not displace traditional legumes, promotion of soybean, diffusion, technological breakthroughs and response to local markets. The implications of these findings are discussed with respect to commonly held views on soybean in Africa.